Tuning the Performance of Negative Tone Electron Beam Resists for the Next Generation Lithography. (27th May 2022) - Lewis, Scott M.; DeRose, Guy A.; Alty, Hayden R.; Hunt, Matthew S.; Lee, Nathan; Mann, James A.; Grindell, Richard; Wertheim, Alex; De Rose, Lucia; Fernandez, Antonio; Muryn, Christopher A.; Whitehead, George F. S.; et al.
Abstract: A new class of electron bean negative tone resist materials has been developed based on heterometallic rings. The initial resist performance demonstrates a resolution of 15 nm half‐pitch but at the expense of a low sensitivity. To improve sensitivity a 3D Monte Carlo simulation is used that utilizes a secondary and Auger electron generation model. The simulation suggests that the sensitivity can be dramatically improved while maintaining high resolution by incorporating appropriate chemical functionality around the metal–organic core. The new resists designs based on the simulation have the increased sensitivity expected and illustrate the value of the simulation approach. Abstract : The exposure sensitivity of negative tone electron beam resists based on a metal–organic ring can be tuned by subtle changes in the chemical composition. Inclusion of unsaturation in organic components and addition of heavy metal ions give a significant increase in write speed.